Semantically Time Tracking of Events from Web Documents - Santos, Welton; Fazzion, Elverton; Dias, Diego; Guimarães, Marcelo; Tuler, Elisa; Rocha, Leonardo (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2021: Proceedings of the 27th Brazilian Symposium on Multimedia and the Web, 2021)
Exploring large news collections created by media outlets with traditional search engines is impractical for demanding users. We propose a temporal exploration tool that aims to facilitate the consultation of news collections. We concentrated our efforts on two fronts: (i) allowing users to make queries with the addition of information from documents represented by word embbedings, and; (ii) retrieving temporal information to generate timelines presented by an appropriate interface. We evaluated our solution in a collection of a Brazilian newspaper, demonstrating that it can draw different timelines, covering different subtopics of the same theme.